Respuesta :

Answer:

c4+8c3+−3c2+−7c

Step-by-step explanation:

Let's simplify step-by-step.

−3c4−5c2−7c+4c4+8c3+2c2

=−3c4+−5c2+−7c+4c4+8c3+2c2

Combine Like Terms:

=−3c4+−5c2+−7c+4c4+8c3+2c2

=(−3c4+4c4)+(8c3)+(−5c2+2c2)+(−7c)

=c4+8c3+−3c2+−7c

Answer:

c^4 + 8 c^3 - 3 c^2 - 7 c

Step-by-step explanation:

(− 3c^4 − 5c^2 − 7c) + (4c^4 + 8c^3 + 2c^2)

I like to line them up vertically.

 − 3c^4            − 5c^2 − 7c

+  4c^4 + 8c^3 + 2c^2

--------------------------------------------

 c^4    +8c^3   -3c^2  -7c

ACCESS MORE